Training of Geography Teachers for Secondary Schools at University in Uganda: An Analysis of Gulu University Teacher Trainees’ Teaching Practice. - Nuwategeka, Expedito; Odama, Stephen (Advances in Social Sciences Research Journal, 2020)
The changes in learner characteristics and the learning environment in the twenty first century calls for adjustments in teacher training to meet the needs of the contemporary learners. This study analyses training of geography teachers at Gulu University with the view of assessing the application of contemporary geography teaching methodologies for the twenty first century learners. Time- series data were collected from teacher trainees’ lesson plans used during school practice running for three consecutive years of 2016, 2017, and 2018. Teaching methods as well as types of instructional materials were extracted from eighty one lessons taught by teacher trainees in thirty six schools in both rural and urban Uganda. Using SPSS 16.0 software, data was analysed to generate frequencies, counts and cross-tabulations. Findings reveal that question and answer method was the most used while guided discovery was the least used, followed by demonstration. Fieldwork and project methods were not used at all. It was also found out that in 12% of all the lessons, there was no use of instructional materials in the teaching/learning process. The study recommends that the curriculum structure of future geography teacher trainees be improved to factor in contemporary teaching styles which use modern teaching equipment relevant to the current generation of technology and learners, and the training of lecturers who mentor geography teacher trainees at universities be institutionalized.